Gu ru drag po Ye śes rab ʼbar : a collection of the rediscovered texts - Kloṅ-gsal-sñiṅ-po, Gter-ston, 1625-1692 (B. Jamyang Norbu, 1971)
Rituals of Kathok, a Nyingmapa monastery in eastern Tibet, and its affiliates.